Trends in the use of commissives in the informal judicial system of Sulha - Mohamed Ayed Ibrahim Ayassrah; Ali Odeh Alidmat (Universitas Syiah Kuala, 2023)
This article investigates the trends in using commissive speech in Sulha proceedings in Jordan. Sulha focuses on a dispute-resolution system in Arab society that uses the Bedouin Arabic dialect as the primary language of communication. Qualitative and quantitative research designs involving descriptive and survey instruments were used in this study. The data for the study were collected as audio recordings of some incidents taken from Sulha samples. Some of the data are from interviews with Sulha participants and the synthesis of archived disputes related to cases previously handled by Sulha. The data analysis was done according to the scope of Speech Act theory to show the trends adopted in the Sulha tribunals in making commitments by different participants in solving disputes. This study finds that the informal legal setting in the Sulha tribunals determines the patterns exhibited by commissive speech acts and their frequencies during the Sulha proceedings. A number of eight commissive speech acts are realised in the Sulha proceedings: promise, swear, vow, threat, guarantee, warning, acceptance, and offer. The eight commissive speech acts are realised either explicitly or implicitly. The results further reveal some of the commissive speech acts can elicit other commissives, and a number of commissives can also be resultant forces of other speech acts, such as the acts of directives. The finding of this study is expected to help understand how forms of language used in the Sulha enhance the adoption and discharge of commitment during the Sulha proceedings.